2012
DOI: 10.1007/s00213-011-2613-9
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and explicit alcohol-related motivations among college binge drinkers

Abstract: Implicit and explicit drinking motivations are differentially associated with problem drinking behaviors. Future research should examine the underlying neurobiological mechanisms associated with these factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Higher scores correspond to more frequent alcohol problems. The RAPI is one of the most widely used measures of alcohol problems among college students (e.g., Herschle, McChargue, Killop, Stoltenberg, & Highland, 2012;Kazemi, Sun, Nies, Dmochowski, & Walford, 2012) and has demonstrated good validity and reliability. RAPI items were recoded as dichotomous before being summed for a total score; thus, scores could range from 0-23.…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores correspond to more frequent alcohol problems. The RAPI is one of the most widely used measures of alcohol problems among college students (e.g., Herschle, McChargue, Killop, Stoltenberg, & Highland, 2012;Kazemi, Sun, Nies, Dmochowski, & Walford, 2012) and has demonstrated good validity and reliability. RAPI items were recoded as dichotomous before being summed for a total score; thus, scores could range from 0-23.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, residential laboratory studies convincingly demonstrated that alcohol consumption was sensitive to increases in response cost and the presence of alternative reinforcers (e.g., Bigelow et al., ; Griffiths et al., ; Sanders et al., ; for a review, see Bigelow, ), key predictions from operant theory. Using self‐report measures, it is also clear that alcohol has both positively reinforcing properties that enhance an experience (e.g., stimulation, self‐perception, social enhancement, gustatory properties) and negatively reinforcing properties that remove unpleasant experiences (e.g., anxiolysis, alleviation of depression) (Carey and Correia, ; Corbin et al., ; Darkes et al., ; Herschl et al., ; Kuntsche et al., ). Importantly, these different forms of positive and negative reinforcement are not mutually exclusive and operate concurrently, reflecting an individual's underlying motivational schemata for alcohol reinforcement.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…It is beyond the scope of this review to unpack the specific findings on an index‐by‐index basis, but, in general, the largest effect sizes in the studies to date have tended to be for intensity and O max , with somewhat smaller relationships for breakpoint and elasticity (e.g., MacKillop et al., ). In terms of interrelationships, the correlations among the indices vary considerably, ranging from negligible to very high (e.g., Herschl et al., ; Murphy and MacKillop, ; Murphy et al., ). However, 2 studies examined the latent structure of these relationships and have found a binary factor structure to the data, with intensity and O max loading on 1 factor and elasticity, breakpoint, and O max loading on the other ( O max loading on both) (Bidwell et al., ; MacKillop et al., ).…”
Section: Three Core Behavioral Economic Assays For Understanding Alcomentioning
confidence: 99%
“…7-9 These expectations have been extensively studied in behavioral medicine and found to affect multiple health behaviors, including alcohol consumption, smoking, and weight management. 10-16 Individuals who consume excessive alcohol may have multiple positive outcome expectancies about its perceived benefits. Examples include social confidence, sexual attractiveness, and general euphoria.…”
Section: Outcome Expectanciesmentioning
confidence: 99%